RESPON PERTUMBUHAN DAN PRODUKTIVITAS KELAPA SAWIT (Elaeis Guineensis Jacquin) TERHADAP KEDALAMAN DAN BOBOT BAHAN ORGANIK PENUTUP BIOPORI PADA TANAH PODSOLIK MERAH KUNING - Umar Battong; Raihani Wahdah; Gusti Rusmayadi (EnviroScienteae, 2018)
This study aims to determine the effect of bokashi and biopori depth treatment on growth and production of oil palm. The study was conducted at Long Gelang Paser Regency in August 2017 - January 2018 using a randomized block design with two factors. The first factor is the depth of biopori with depth: 50, 75, and 100 cm and the second factor is bokashi weight with level: 4, 5 and 6 tons per hectare with three replicates, highest weight of TBS obtained at 75 cm biopori depth, obtained at a depth of 100 cm biopori with 6 ton per hectare of bokashi, the highest soil N content was obtained at 50 cm depth with treatment of 6 tons per hectare bokashi, the highest groundwater content was obtained at 75 cm biopori depth with bokashi 4 tons per hectare